RESPON ANAK KORBAN KEKERASAN TERHADAP PROGRAM PELAYANAN SOSIAL OLEH PUSAT KAJIAN DAN PERLINDUNGAN ANAK (PKPA) - Intan DIRJALAILA (Welfare StatE, 2013)
Abuse is a word commonly translated as violence, persecution, torture or mistreatment. Child Abuse can be defined as an  event of physical injury, mental, or sexual abuse which usually done by people who have a responsibility for the welfare of the child. Which is indicated by losses and threats to the health and welfare of children. This study aims to determine how the respond of child victims of physcal, psycilogical, sexual and social violence of social service programs by PKPA. Response mean that a behavior or attitude either pre tangible detailed understanding, assessment, or impact resistance, like it or not and the use of a phenomenon certain. In this case the child response directed against Revenue Service complaints, the Legal Services program, counseling, Monitoring Health Condition and Monitoring Of Case. Based of analysis of case it can be concluded that the child victims of violence assistance PKPA give excellent response in all social services. Each victim can know and understand about the purpose of social service and to follow procedures. Victims actively involved in following stages help since the reception  service complaints to the monitoring service. Through a series of social service activities designed by teh PKPA, Victims and families can be feel positive benefit from social service by PKPA in resolve cases of violence being faced and give best value against the implementation of social service program by PKPA. Keyword : Child Response and Social Service